Strategic Marketing Approach of Indonesia Aluminium Mineral Industry: Upstream and Downstream Analysis - Sri Bramantoro Abdinagoro; Mohammad Hamsal (Bina Nusantara University, 2022)
The research aimed to determine the causes of imports by analyzing the upstream and downstream sides of the existing aluminium industrial chain. The research applied a descriptive-exploratory approach by collecting secondary data from credible sources. Interviews and focus group discussions with appropriate experts were also conducted to obtain supporting data. Research shows that aluminium imports will continue both in the short and long term. It is due to the upstream supply, especially in aluminium smelters, which cannot keep up with the increasing demand. Even though the market opportunity, especially in the automotive, construction, and power cable segments, is enormous and continues to grow, if there is not enough supply, the deficit of aluminium metal will continue to occur. It takes encouragement from the Government's political will to provide ease of electricity sources, increase production capacity and technology, change the mindset from relying on traders solely towards the mindset of the industrialist.